233 Use of mobile phones and light metre applications in the assessment of the occupational lighting environment. (24th April 2018) - Lee, So Young; Pisaniello, Dino; Gaskin, Sharyn; Piccoli, Bruno
Abstract : Introduction: With a variety of built-in sensors, smartphone users can do many things with only one portable device. Light metre applications measure illuminance and are offered free or at low cost. Like noise metre apps, it is tempting to use such devices for preliminary lighting surveys. However, there are few reports of studies evaluating such use, and none which have explored their potential use for blue light hazards. This paper presents preliminary data on side by side measurements of illuminance and blue light hazard (BLHF) function-weighted illuminance with a range of smartphones, apps and light sources. Methods: Phones with Android and Apple iOS operating systems and two phone apps were compared alongside a professional lux metre on a workstation desk in a mock office, set up in a dark room. A blue light filter (Hoya B440) was used directly over the sensors for the approximate BLHF weighted value. Results: The values of the illuminance and blue-weighted illuminance differed depending on distances and the types of light sources. The illuminance values for Android and Apple devices using the same software were variable suggesting differences in sensor hardware or circuitry. There were major differences between forward and rear facing sensors. The use of the blue light filter significantly reduced illuminance readings, limiting practical application for some devices. Discussion: The rationale for the use of BLHF filters on photometric instrumentation for blue light hazard assessment has been described in the literature. Calibration factors for both naked and filtered sensors need to be established for specific phones and software. The limitations and variances of particular combinations also need to be understood. However, in principle, the use of a smartphone in preliminary lighting surveys may be feasible, and if so, guidance for their use may be developed.